Role of Endothelial Function in the Pathogenesis of Essential Hypertension in Children - N.N. Kaladze; T.Yu. Yanina (Zaslavsky O.Yu., 2013)
This review covers the pathogenic mechanisms that contribute to high blood pressure from the position of vascular endothelial dysfunction. Major functional changes in the vascular endothelium as an imbalance between the production of vasodilating, vasoconstrictor and antiproliferative factors of vascular wall. Endothelial dysfunction is considered as a criterion for remodeling of the cardiovascular system in hypertension.